Compliance with the NATO Standards in the Field of Psychological Assistance for the Servicemen with Post-Traumatic Stress Disorder - Druz, Oleh; Androsovych, Kseniia; Halchenko, Viktoriia; Semencha, Liudmyla; Snyatkova, Tetyana (International Journal of Statistics in Medical Research, 2024)
The increasing number of the servicemen with post-traumatic stress disorder (PTSD) as a result of the war raises the problem of providing them with psychological assistance among the top priorities at the national level. The aim of the study is to identify the effectiveness of using NATO standards in the system of psychological assistance to the servicemen with PTSD. Methods: The study employed the Mississippi Scale, Impact of Event Scale (IES-R), Hospital Anxiety and Depression Scale (HADS). The statistics were processed using descriptive statistics, analysis of variance, Student’s t-test for independent samples. Results: The study showed that 20.28% of the servicemen had a high level of PTSD. They have pronounced symptoms of intrusion, avoidance, hyperarousal, high anxiety, and depression. It was established that the use of NATO standards of psychological assistance to the servicemen with PTSD is reliably effective in reducing symptoms of intrusion (t=2.53, p≤0.01), avoidance (t=3.22, p≤0.01), excitability (t =4.18, p≤0.01), anxiety (t=4.56, p≤0.01), and depression (t=3.87, p≤0.01).Conclusions. The problem of the occurrence of PTSD and symptoms of the disorder among the servicemen participating in military operations was confirmed. It was proved that the use of NATO standards in the training and psychological assistance to service men is effective in reducing the PTSD level and its symptoms. Prospects: The obtained results are significant for military psychologists who work directly with the servicemen in warfare and can use the obtained data for early intervention to prevent the occurrence of PTSD.